II-21 Interfering with interferon in lupus: hitting the sweet spot with CNTO 6358. (31st August 2016) - Jordan, Jarrat; Cesaroni, Matteo; Schreiter, Jessica; Huang, Chichi; Chevrier, Marc; Benson, Jacqueline
Abstract : Background: The type I interferon (IFN-I) family of cytokines is thought to play a central role in the pathogenesis of systemic lupus erythematosus (SLE) and therapeutic approaches to down-modulate this pathway have demonstrated clinical efficacy. The IFN-I pathway is composed of multiple closely related IFN-α subtypes and single functional molecules for IFN-β, IFN-ε, IFN-κ and IFN-ω. Some members of the IFN-I family are thought to contribute to SLE pathogenesis, while others may be more relevant for host defense. We developed a fully-human monoclonal antibody (CNTO 6358) to selectively neutralise the predominant soluble IFN-Is expressed in SLE, while retaining the functions of IFN-β. Here we demonstrate in vitro bioactivity using endogenous SLE patient-derived IFN-I preparations, including immune complexes and serum/plasma from racially diverse SLE populations, providing evidence that the neutralisation and potency profile of CNTO 6358 may enable potent suppression of IFN-Is prevalent in SLE without suppression of other IFN-Is more essential for other host defense processes. We further describe an in vitro assay that may enable the prediction of responders and non-responders with CNTO 6358, providing a transformational framework for SLE precision medicine. Materials and methods: Pooled SLE serum and plasma or conditioned media from cells exposed to pooled SLE patient immune complexes or recombinant human IFN-Is were utilised as stimuli in an ISRE reporter gene assay (RGA) in the presence of CNTO 6358 or control. SLE patient whole blood was incubated in vitro for 24 hours in the presence or absence of CNTO 6358 and the impact of inhibitor treatment on gene expression was determined by RNA-Seq relative to untreated healthy donor samples. Results: IFN-I activity present in plasma and serum preparations from multiple SLE cohorts and activity present in conditioned media from PBMCs exposed to SLE patient immune complexes was neutralised to levels seen in healthy control samples. The in vitro addition of CNTO 6358 to blood from individual SLE patients enabled the identification of donors having robust normalisation of baseline elevated IFN-I signature gene expression and those having moderate to minimal transcriptional changes. Conclusions: CNTO 6358 exhibited potent neutralisation of multiple SLE patient-derived IFN-I preparations, demonstrating a bioactivity profile targeting the most prevalent IFN-I subtypes elevated in SLE patients, while preserving the functionality of other IFN-Is which may be more important for host defense. Furthermore, our in vitro assay and in silico methodologies may enable prediction of responders to our treatment, providing a transformational framework for SLE precision medicine.